Decidual natural killer cell receptor expression is altered in pregnancies with impaired vascular remodeling and a higher risk of pre-eclampsia - Wallace, Alison E. (Society for Leukocyte Biology, 2015)
HLA-interacting cell surface receptors are altered on decidual natural killer cells in pregnancy, potentially altering interactions with fetal cells via chemokine expression.